2016
DOI: 10.1371/journal.pone.0167468
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein (HDL) Counter-Regulates Serum Amyloid A (SAA)-Induced sPLA2-IIE and sPLA2-V Expression in Macrophages

Abstract: Human serum amyloid A (SAA) has been demonstrated as a chemoattractant and proinflammatory mediator of lethal systemic inflammatory diseases. In the circulation, it can be sequestered by a high-density lipoprotein, HDL, which carries cholesterol, triglycerides, phospholipids and apolipoproteins (Apo-AI). The capture of SAA by HDL results in the displacement of Apo-AI, and the consequent inhibition of SAA’s chemoattractant activities. It was previously unknown whether HDL similarly inhibits SAA-induced sPLA2 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Regulatory effects of HDL supplementation on SAA's pro-inflammatory bioactivity, including mitigation of production of reactive oxygen species, has been reported in isolated murine macrophage cultures [22,41]. However, in vivo studies on the role of HDL/SAA interactions in complex biological environments are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory effects of HDL supplementation on SAA's pro-inflammatory bioactivity, including mitigation of production of reactive oxygen species, has been reported in isolated murine macrophage cultures [22,41]. However, in vivo studies on the role of HDL/SAA interactions in complex biological environments are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive in ammation is one of the important features of COVID-19 patients, especially in severe and died patients [24,25,26,27], usually manifested by a marked increase in in ammatory factors, such as CRP and interleukins [3,28]. HDL-C is believed to have an inhibitory effect on in ammation [29,30,31]. In this study, patients with low HDL-C showed a higher level of CRP, which suggested that HDL-C may inhibit the in ammatory response and thus play a protective role in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…One important finding is that HDLs stimulate the transcriptional regulator ATF3, which downregulates inflammatory pathways that may in turn decrease the inflammatory response in case of sepsis [34]. Moreover, Zhu et al have shown in murine macrophages that human serum amyloid A (SAA) dramatically upregulates the expression and secretion of a group of phospholipases (sPLA2-IIE and sPLA2-V), which are late pro-inflammatory mediators family [35]. In this in vitro study using purified HDL, HDL dosedependently attenuated SAA-induced secretion of both sPLA2-IIE and sPLA2-V. Lastly, Suzuki et al demonstrated that HDLs inhibit a subset of LPS-stimulated macrophage genes that regulate the type I interferon response, independently of sterol metabolism, raising the possibility that regulation of macrophage transcriptome by HDLs might link innate immunity to cardioprotection [36].…”
Section: Regulation Of Inflammatory Response In Macrophagesmentioning
confidence: 99%